Lipid mobilization assessment in transition dairy cattle using ultrasound image biomarkers (2015)
Excessive lipid mobilization during the transition period of dairy cows predisposes animals to higher disease incidence and reduces lactation performance. Plasma non-esterified fatty acids (NEFA) are used as a marker of lipid mobilization intensity to monitor transition cow management and as a disease risk predictor. NEFA evaluation can be complemented by continuous monitoring of adipose tissue depth reductions during the transition period using ultrasound images of the retroperitoneal (RPAT) and subcutaneous adipose tissue (BFAT) depots. These image biomarkers are easily obtainable and their real time nature offers an important advantage that could help improve transition cow health programs. The objective of this study was to evaluate the use of both RPAT and BFAT ultrasound measurements as quantitative image biomarkers and its association with plasma NEFA. A longitudinal cohort study evaluated adipose image biomarkers in 44 Holstein cows in a commercial dairy herd. Ultrasound examination and blood samples collection were performed at 4 (dry) and 2-3 (close-up) weeks before expected calving date, and at 1 (calving) and 4 (lactation) weeks after parturition. Both RPAT and BFAT depth measurements were significantly lower at parturition and at the lactation samples compared to pre-calving measures and were negatively associated with plasma NEFA. Only BFAT predicted minimum concentrations of plasma NEFA before and after calving. The use BFAT as an image biomarker of lipid mobilization and its risk predictive value in other herds with different management styles requires further investigation. © 2015 Elsevier B.V.